O consumo de psicoativos entre mulheres brasileiras e associações com comportamentos de riscos: dados do I e II Levantamento Nacional de Álcool e Drogas (LENAD) - Massaro, Luciana Teixeira Dos Santos [UNIFESP] (2018)
Introduction: Several studies point out that consumption of licit and illicit drugs is on the rise among Brazilian women, specially alcohol and amphetamine-type stimulants (ATS). This population is particularly more vulnerable, not only to the physiological effects of psychoactive substances consumption, but also to the exposure of many consumption-related risks. Objectives: This study tackles these issues, exploring the use of substances by this population and the factors associated with use via three studies described in the following scientific publications. Study 1: The study described the consumption of ATS in a national sample of the Brazilian population and investigated possible differences among gender, and associations of levels of consumption with sociodemographic factors, and with the use of other psychoactive substances. Study 2: It described and compared the alcohol consumption prevalence rates in a nationally representative sample of Brazilian women between 2006 and 2012, and analysed associations with unprotected sex, early pregnancy and abortion. Study 3: It presented the prevalence rates of rape in Brazil and investigated its associations with alcohol consumption. Method: All three studies were carried out through data analysis of two waves of the Brazilian National Alcohol and Drugs Survey (BNADS), performed in 2006 and in 2012, with nationally representative home samples of the Brazilian population, with 3,007 individuals in 2006, and 4,607 in 2012. The work investigated the consumption of licit and illicit psychotropic substances, as well as the main risk factors related to physical and mental health and risk behaviours. The three studies used different subsamples of the original sample of 7,614 individuals. Study 1: Subsample of LENAD II with 3,828 individuals, aged between 15 and 64 years old. Study 2: Subsample of 4,256 women, 14 years old and older, with 1,719 respondents of 2006, and 2,537 of 2012. Study 3: Subsample of LENAD II with 4,283 respondents, aged 14 years old and older, with 1,918 men and 2,365 women. Multivariate analyses using different weighted regression models were chosen to calculate odds (odds ratios- OR), adjusted for the associations in the three studies using Stata 13. Studies 1 and 2 presented structural equation modelling (SEM), using PROCESS (version 2.16) for SPSS (version 21.0) and MPlus (version 7.4), respectively. Results: Study 1: The prevalence rates of lifetime and last year ATS use among the general Brazilian population were 4.1% and 1.6%, respectively. Higher income individuals and users of other psychoactive substances presented higher chances of ATS use. Higher level of education was identified as a protecting factor, decreasing the chances of ATS consumption. The conditional model showed that concomitant cocaine use cancelled out that protective effect. Study 2: The prevalence rate of binge drinking among women was 35.1% and 47.1% in 2006 and 2012, respectively, a significant increase, especially among women aged 40 to 59 years old. There was no significant difference in the period in terms of the prevalence of alcohol use disorder among women in Brazil. Binge drinking (without alcohol use disorder) was found to increase the odds of unprotected sex and abortion. The path analysis showed that early pregnancy was a mediator of the relationship between alcohol consumption and abortion. Study 3: The prevalence rate of rape among the Brazilian population older than 14 years old was estimated as 2.6%, with 1.7% among men and 3.5% among women. For both sexes, the highest prevalences were concentrated among those aged between 26 and 59 years (3.3%), those with low educational levels (3.8%), and those who were single, divorced or widowed (3.1%). Among individuals who were diagnosed with alcohol use disorder, according to the DSM-5 (Diagnostic and Statistical Manual of Mental Disorders), 6% reported having been raped, as did 3.3% of those who reported binge drinking. Logistical and multivariate regression analyses showed that, for both women and men, age (those between 26 and 59 years), marital status (single), alcohol use disorder and binge drinking are factors associated with an increased probability of being raped, whereas a higher educational level (more than 9 years of schooling) was shown to be capable of reducing the odds of being raped. Conclusions: The results provide a broad view on the consumption of different substances among the Brazilian population, focusing on the exposure to the risk behaviours related to the consumption of psychoactive substances. The work explores how the consumption of substances has a negative impact on the psychosocial welfare of individuals. The knowledge of the risks associated with the researched outcomes is fundamental to the formulation of prevention strategies. The implementation of such strategies applied to substance use and violence are of crucial importance, since they can ease the problems related to this scenario, by promoting quality of life to the population, and at the same time reducing the costs of the health care system.